Quantitative trait mapping in Diversity Outbred mice identifies novel genomic regions associated with the hepatic glutathione redox system - Rebecca L. Gould; Steven W. Craig; Susan McClatchy; Gary A. Churchill; Robert Pazdro (Redox Biology, 2021)
The tripeptide glutathione (GSH) is instrumental to antioxidant protection and xenobiotic metabolism, and the ratio of its reduced and oxidized forms (GSH/GSSG) indicates the cellular redox environment and maintains key aspects of cellular signaling. Disruptions in GSH levels and GSH/GSSG have long been tied to various chronic diseases, and many studies have examined whether variant alleles in genes responsible for GSH synthesis and metabolism are associated with increased disease risk. However, past studies have been limited to established, canonical GSH genes, though emerging evidence suggests that novel loci and genes influence the GSH redox system in specific tissues. The present study marks the most comprehensive effort to date to directly identify genetic loci associated with the GSH redox system. We employed the Diversity Outbred (DO) mouse population, a model of human genetics, and measured GSH and the essential redox cofactor NADPH in liver, the organ with the highest levels of GSH in the body. Under normal physiological conditions, we observed substantial variation in hepatic GSH and NADPH levels and their redox balances, and discovered a novel, significant quantitative trait locus (QTL) on murine chromosome 16 underlying GSH/GSSG; bioinformatics analyses revealed Socs1 to be the most likely candidate gene. We also discovered novel QTL associated with hepatic NADP+ levels and NADP+/NADPH, as well as unique candidate genes behind each trait. Overall, these findings transform our understanding of the GSH redox system, revealing genetic loci that govern it and proposing new candidate genes to investigate in future mechanistic endeavors.